The Evolution of Nepal's Foreign Policy in a Dynamic Political Landscape - Ghimire, Tara Nath (Historical Journal, 2023)
Foreign policy is a vital part of national policy. Foreign policy is the cornerstone of any sovereign country's foreign relations. The foreign policy of Nepal has been implemented in the same manner despite the changing circumstances in the country. The current constitution with an updated structure has come into force. In addition to the design of the constitution, Nepal's governance system has also been altered. Even in the changing context, Nepal has continued its old foreign policy. A country's foreign policy also plays an important role in its development. Nepal's foreign policy has always been guided by its primary interests. Research should be conducted to determine why the situation could not be changed. Nepal's foreign policy is based on its initial interests. During this study, the effect of foreign policy with primary and secondary interests on the development of the country as well as the current foreign policy of Nepal have been examined. In this study, only secondary data is used, and it is qualitative in nature. Data and facts derived from secondary sources were gathered from the library and related literature reviews. To conclude, the data is interpreted and analyzed in the context of Nepal's foreign policy considering the changing political situation.